Grammaticalized modal auxiliaries in Modern Standard Arabic: A semantic and morphosyntactic analysis - Hanaa Samaha; Elham Ghobain (Universitas Syiah Kuala, 2026)
Widely agreed to be universal across languages, modal auxiliaries (MXs) usually develop from open-class lexical verbs that have shifted into closed-class auxiliaries through the process of grammaticalization. The literature on Arabic MXs revealed that MXs as grammaticalized verbs have either been insufficiently explored or explicitly rejected as auxiliaries. From a synchronic perspective, this study aimed to examine the semantic and morphosyntactic properties of seven verbs claimed to have been grammaticalized as MXs in Modern Standard Arabic (MSA). The analysis was guided by a comparison with two other non-modal verbs, ‘yastaṭī’’ and ‘yaqdir’ (can/able). The data were selected from five written articles drawn from four daily Arabic newspapers, with a few examples borrowed from Bardi’s thesis (2008). Semantically, we argued that these MXs have lost their original action-denoting senses when they co-occur with other lexical verbs in their imperfective forms to express modality. Morphosyntactically, this argument was supported by evidence that these MXs show certain restrictions in terms of distribution, negation, finiteness, morphological inflection for passivization and imperatives, and agreement with their subjects in person, number, and gender. This study is significant because its findings establish preliminary systematic criteria for identifying elements claimed to be grammaticalized auxiliaries in MSA. The study implies that languages, such as MSA, may selectively recruit certain lexical verbs to develop grammatical functions; however, the motivations underlying such selectivity remain difficult to determine.